Contribution of dogs to white‐tailed deer hunting success1. Issue 2 (4th October 2012) - Godwin, Christopher; Schaefer, James A.; Patterson, Brent R.; Pond, Bruce A.
Abstract: Dogs ( Canis familiaris ) are used in hunting white‐tailed deer ( Odocoileus virginianus ) in 10 North American jurisdictions. Although the practice is longstanding and controversial, the effects of dogs on the outcome of the hunt have rarely been studied. We evaluated the influence of dogs on recreational hunting of white‐tailed deer based on long‐term data from southeastern Ontario, Canada. Over 25 years, annual surveys of hunters were used to collect data on hunting effort and deer harvest from approximately 85 camps, roughly half of which had dogs. We investigated the relationship between harvest and 3 treatments (i.e., 0 dogs, 1 dog, and ≥2 dogs in camp), interactions with weather and deer density, and effects of neighboring camps. Dogs enhanced hunter success. We found no difference in deer encounter rates but, per unit effort, camps with ≥2 dogs harvested 0.013 (26%) more deer per hunter‐day, missed 0.010 (23%) more deer per hunter‐day, and wounded 0.002 (40%) more deer per hunter‐day than camps without dogs. Conversely, camps without dogs saw, without shooting at, 0.033 (23%) more deer per hunter‐day than camps with ≥2 dogs. These results are consistent with the idea that hunters with dogs are less selective. Hunters with dogs harvested more fawns per unit effort, but we found no difference in the harvest rate of older female deer. More precipitation, greater wind speed, lower temperatures and greater deer density improved harvest success but had no differential effect among dog treatments. Hunter success at camps with ≥2 dogs was less when neighboring camps also had ≥2 dogs. Because antlerless deer quotas are the principal means to control populations, increasing use of hunting dogs is unlikely to have substantial effects in managing overabundant deer. © 2012 The Wildlife Society.